2023
DOI: 10.1186/s12984-023-01134-7
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of overground robotic training versus conventional locomotor training in people with spinal cord injury

Abstract: Background Few, if any estimates of cost-effectiveness for locomotor training strategies following spinal cord injury (SCI) are available. The purpose of this study was to estimate the cost-effectiveness of locomotor training strategies following spinal cord injury (overground robotic locomotor training versus conventional locomotor training) by injury status (complete versus incomplete) using a practice-based cohort. Methods A probabilistic cost-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…A total of 23 records were assessed for eligibility, with 8 being excluded for different reasons (conference papers and studied diseases other than neurological disorders). Finally, 15 studies [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] were included in the systematic review and were appraised for quality ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 23 records were assessed for eligibility, with 8 being excluded for different reasons (conference papers and studied diseases other than neurological disorders). Finally, 15 studies [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] were included in the systematic review and were appraised for quality ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 15 studies with 1634 patients were included in this review (1108 individuals who experienced a stroke and 99 with a spinal cord injury for robotic studies; 367 people who experienced a stroke, 30 with multiple sclerosis and 30 with cerebral palsy for virtual reality studies). Ten papers were focused on robotics [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and five on virtual reality [ 28 , 29 , 30 , 31 , 32 ] ( Figure 2 ). The studies showed a greater predominance of men than women.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations